Response and Disease Dynamics in Untreated Metastatic Colorectal Cancer With Bevacizumab-Based Sequential vs. Combination Chemotherapy—Analysis of the Phase 3 XELAVIRI Trial - Kurreck, Annika; Heinemann, Volker; Fischer von Weikersthal, Ludwig; Decker, Thomas; Kaiser, Florian; Uhlig, Jens; Schenk, Michael; Freiberg-Richter, Jens; Peuser, Bettina; Denzlinger, Claudio; Graeven, Ullrich; Heinrich, Kathrin; et al. (Frontiers in Oncology, 2022)
Introduction: Early tumor shrinkage (ETS), depth of response (DpR), and time to DpR represent exploratory endpoints that may serve as early efficacy parameters and predictors of long-term outcome in metastatic colorectal cancer (mCRC). We analyzed these endpoints in mCRC patients treated with first-line bevacizumab-based sequential (initial fluoropyrimidines) versus combination (initial fluoropyrimidines plus irinotecan) chemotherapy within the phase III XELAVIRI-trial. Methods: DpR (change from baseline to smallest tumor diameter), ETS (≥20% reduction in tumor diameter at first reassessment), and time to DpR (study randomisation to DpR-image) were analyzed. We evaluated progression-free and overall survival with ETS as stratification parameter according to treatment arm, molecular subgroup, and sex. Results: In 370 patients analyzed, a higher rate of ETS (60.9% vs. 43.5%; p=0.001) and significantly greater DpR (-40.0% vs. -24.7%; p<0.001) were observed in the initial combination therapy arm. The improvement was pronounced in RAS/BRAF wildtype tumors. ETS correlated with improved survival irrespective of treatment arm (PFS: p<0.001; OS: p=0.012) and molecular subgroup (PFS: p<0.001; OS: p<0.001). Male in contrast to female patients with ETS had survival benefit (PFS: p<0.001, HR 0.532; OS: p<0.001, HR 0.574 vs. PFS: p=0.107; OS: p=0.965). Conclusions: Initial irinotecan-based combination therapy with bevacizumab improved ETS and DpR in mCRC patients with a particularly high irinotecan-sensitivity of RAS/BRAF wildtype tumors. ETS seems to be a suitable prognostic marker for fluoropyrimidine- and bevacizumab-based combinations in mCRC. This finding was rather driven by male patients, potentially indicating that ETS might be less predictive of long-term outcome in an elderly, female population.